Metabolismo de óxido nítrico, anión superóxido y peroxinitrito en mitocondrias de corazón : participación del complejo I y de la mtNOS en mecanismos de disfunción mitocondrial - Bombicino, Silvina Sonia (2016)
The aim of this work was to study the functional interaction between complex I and mitochondrial nitric oxide synthase (mtNOS) in heart mitochondria. In physiological situations, mtNOS was able to use complex I as an electron donor, under reverse electron flow of the respiratory chain. In myocardial stunning and diabetes, mitochondrial dysfunction was observed with changes in the activities of complex I and mtNOS. In myocardial stunning a decrease in mitochondrial state 3 respiration sustained by malate-glutamate and in complex I and mtNOS activities; and an increase in H2O2 production, lipid and protein oxidation, and tyrosine nitration were observed. This pattern is in agreement with ?complex I syndrome?. The mitochondrial dysfunction in diabetes included the decline in mitochondrial respiration, in respiratory complexes activities, and in ATP production; with an enhancement in H2O2 and NO generation and mtNOS expression. The increase in NO production and NO steady state concentration in the mitochondrial matrix and its diffusion to cytosol may be the molecular signaling involved in the mitochondrial biogenesis process, triggered to supply the energetic requirements of the heart. The association between complex I and mtNOS might be one of the NO regulatory mechanisms on the respiratory chain and could explain the pathogenesis of diseases associated to ?complex I syndrome?.